LIVING AND LEARNING (Fiep Bulletin - online, 2016)
The issue of learning disabilities is debated worldwide. In Brazil and Latin America has gained alarming proportions. Prepare the student to learn how to learn. Theoretical and methodological perspectives of human development and learning.The life cycle. Psychopathological processes in human development. Modes of learning and its relation to the teaching process.Contributions of neuroscience in understanding human development and learning. We will seek to understand the neurological underpinnings specifically the nervous system and its functional units. Analyze the relationships between physiological, psychological, social and cultural aspects of human development and. Enabling professionals to work more understanding on the inclusion of people with disabilities in different institutions. Characterize the relationships between education, learning and neuroplasticity contemplating weaknesses: physical, visual, hearing and mental. Deepening knowledge about chronic diseases; disorders or learning disorders.Brain neuropathology, their cognitive disorders and their neuropsychological and socio-cultural implications.
Keywords: Learning Difficulties; Neuroscience.